2012
DOI: 10.3892/or.2012.1717
|View full text |Cite
|
Sign up to set email alerts
|

Jolkinolide B induces apoptosis in MDA-MB-231 cells through inhibition of the PI3K/Akt signaling pathway

Abstract: Abstract. The phosphoinositol-3-kinase (PI3K)/Akt signal transduction pathway is critically important for tumor cell growth, proliferation and apoptosis. Apoptosis activation has been reported to be a good target in cancer therapies. In this study, we have found that jolkinolide B (JB), a diterpenoid from the traditional Chinese medicinal herb Euphorbia fischeriana Steud, strongly inhibited the expression of the PI3K p85 subunit and the phosphorylation of Akt. Furthermore, we evaluated the effects of JB on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…AdsiBMP9 induced proliferation and invasion were reversed by these inhibitors, suggesting that BMP9 affects cell proliferation via the ERK1/2 and PI3K/AKT signaling pathways. These results are consistent with those from previous studies, demonstrating that ERK1/2 and PI3K/AKT signaling pathways play crucial roles in the proliferation and invasion of breast cancer cells [34], [35]. All these findings demonstrate that ERK1/2 and PI3K/AKT signaling pathways are involved in the BMP9 mediated inhibition of proliferation and invasion of SK-BR-3 cells.…”
Section: Discussionsupporting
confidence: 93%
“…AdsiBMP9 induced proliferation and invasion were reversed by these inhibitors, suggesting that BMP9 affects cell proliferation via the ERK1/2 and PI3K/AKT signaling pathways. These results are consistent with those from previous studies, demonstrating that ERK1/2 and PI3K/AKT signaling pathways play crucial roles in the proliferation and invasion of breast cancer cells [34], [35]. All these findings demonstrate that ERK1/2 and PI3K/AKT signaling pathways are involved in the BMP9 mediated inhibition of proliferation and invasion of SK-BR-3 cells.…”
Section: Discussionsupporting
confidence: 93%
“…In past decades, many natural products including berberine [ 21 ], resveratrol [ 22 ] and quercetin [ 23 ] were found to exhibit significant anti-cancer effects and thus were applied in clinic. Jolkinolide B, a diterpenoid compound isolated from the dried plant roots of Euphorbia Fscheriana Steud, has previously been reported to have anticancer effects on cancer, such as inhibiting the proliferation of mouse melanoma [ 13 ], inducing the apoptosis of breast cancer [ 24 , 25 ] and prostate cancer [ 26 ], and suppressing the metastatic activity of breast cancer cells [ 10 ]. As determined here, the IC50 of JB against CRC (18.25–38 ”M, 48 h) is comparable to or smaller than those well-known promising agents including resveratrol (164.7 ÎŒM, 48 h) [ 27 ], quercetin (81.65 ± 0.49 ÎŒM, 48 h) [ 28 ] or some first line chemotherapy (5-FU, 92.85 ”M, 72 h) [ 29 ], we speculate that JB could be a potential anticancer agent for CRC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 1 , an ent -abietane type diterpenoid extracted from plants of the E. fischeriana, has been reported to exhibit promising anticancer activity by activating apoptosis in solid and liquid tumors, including human Leukemic, breast cancer and mouse melanoma [ 17 , 18 , 21 , 22 , 23 ]. At the molecular level, Jolkinolide B was found to inhibit JAK2/STAT3 pathway in human Leukemic HL-60 and THP-1 cells [ 21 ].…”
Section: The Anti-cancer Mechanism Of Diterpenoidsmentioning
confidence: 99%
“…Compound 1 treatment led to downregulation of JAK2/STAT3 and bcl-2 and upregulation of Bax and cytosolic cytochrome c, thus triggering caspase-3, -8 and -9 activation-mediated apoptotic induction. On the other hand, compound 1 can interfere with PI3K/Akt pathways, leading to cancer cell apoptosis in MDA-MB-231 cells and Human Leukemic U937 cells [ 18 , 19 ]. In addition, a novel mechanistic finding showed that Jolkinolide B induced apoptosis in mouse melanoma B16F10 cells by altering glycolysis [ 23 ].…”
Section: The Anti-cancer Mechanism Of Diterpenoidsmentioning
confidence: 99%